B chromosomes: from cytogenetics to systems biology - Valente, Guilherme T. [UNESP]; Nakajima, Rafael T. [UNESP]; Fantinatti, Bruno E. A. [UNESP]; Marques, Diego F. [UNESP]; Almeida, Rodrigo O. [UNESP]; Simões, Rafael P. [UNESP]; Martins, Cesar [UNESP] (Springer Nature, 2017)
Though hundreds to thousands of reports have described the distribution of B chromosomes among diverse eukaryote groups, a comprehensive theory of their biological role has not yet clearly emerged. B chromosomes are classically understood as a sea of repetitive DNA sequences that are poor in genes and are maintained by a parasitic-drive mechanism during cell division. Recent developments in high-throughput DNA/RNA analyses have increased the resolution of B chromosome biology beyond those of classical and molecular cytogenetic methods; B chromosomes contain many transcriptionally active sequences, including genes, and can modulate the activity of autosomal genes. Furthermore, the most recent knowledge obtained from omics analyses, which is associated with a systemic view, has demonstrated that B chromosomes can influence cell biology in a complex way, possibly favoring their own maintenance and perpetuation.
Keywords: Cytogenomics; Evolution; Genomics; Supernumerary chromosomes